If it's not what You are looking for type in the equation solver your own equation and let us solve it.
1+28x=0.5(59x-1)
We move all terms to the left:
1+28x-(0.5(59x-1))=0
We calculate terms in parentheses: -(0.5(59x-1)), so:We get rid of parentheses
0.5(59x-1)
We multiply parentheses
29.5x-0.5
Back to the equation:
-(29.5x-0.5)
28x-29.5x+0.5+1=0
We add all the numbers together, and all the variables
-1.5x+1.5=0
We move all terms containing x to the left, all other terms to the right
-1.5x=-1.5
x=-1.5/-1.5
x=1
| 4.3x-3.9=21.9 | | -d+7=-2d-3 | | 7m=27 | | (2x)/(5)+3x=12^(2x+5) | | 125x-75x+38,200=40,000-150x | | 13p=8p-15 | | 2/10b=95 | | 2m+1=3m+4(m-1 | | y+2.3=4.7 | | x2+2=7 | | -7+s=8+6s | | f2=5/8 | | 41-90=x | | 4−3y=-6 | | (8x-20)+(3x+2)=180 | | -2x=x+27 | | 1/3m-4=2 | | 5=|-8-8x| | | 3(y-5)-5=-21 | | 6/k+3=6/k-7 | | 20+30b=-20 | | x+2x3=27 | | 10-2y+10=y-10 | | 110-5x=180 | | 4x=(34+102)° | | 3+y+20=95 | | n-38=25 | | 5.8x+5=3.8x+17 | | Y=-16x2+9x+4 | | 24=6-2(b-3) | | 7d-6=3d+10 | | Y=16x2+9x+4 |